(untitled) (International Journal of Engineering and Computer Science, 2018)
Since the development of New Austrian Tunneling Method (NATM), shotcrete in tunnels has been widely applied. It’s most important features are durability, speed of application and cost effectiveness. The New Austrian Tunnelling Method (NATM) is characterized by the continuous adaption of driving parameters, such as unsupported length (i.e., the distance between the tunnel face and the shotcrete lining, excavation rate, etc.) to the observed response of the already-excavated part of the tunnel. In order to devise such tables, two different arch sections, together with three different overburden types, were considered. Some Geotechnical parameters such as apparent cohesion and angle of internal friction of surrounding rocks were chosen, based on the five-category classification of Bieniawski. Two K0 factors (the ratio of horizontal stress to vertical stress) and an average rock density were utilized. Using numerical methods, 60 models were then devised in this way.